2009
DOI: 10.1016/s1658-3876(09)50035-0
|View full text |Cite
|
Sign up to set email alerts
|

Acinic cell carcinoma of the salivary glands: A literature review

Abstract: Acinic cell carcinoma (ACC) is a low-grade malignant salivary neoplasm that constitutes approximately 17% of primary salivary gland malignancies. In the head and neck region, the parotid gland is the predominant site of origin and women are usually more frequently diagnosed than men. Previous radiation exposure and familial predisposition are some of the risk factors for ACC. A slowly enlarging mass lesion in the tail of the parotid gland is the most frequent presentation. The diagnosis is usually confirmed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
124
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(132 citation statements)
references
References 45 publications
7
124
0
1
Order By: Relevance
“…It accounts for approximately 5% to 17% of all salivary gland tumors and 10% to 17% of all malignant salivary gland tumors [28,[36][37][38]. The parotid gland is composed almost exclusively of serous type acini, and it is the most common site of AcCC (80% to 90% of cases); other reported sites are the palate (up to 15%), submandibular gland (4%), and sublingual gland (1%).…”
Section: Acinic Cell Carcinomamentioning
confidence: 99%
“…It accounts for approximately 5% to 17% of all salivary gland tumors and 10% to 17% of all malignant salivary gland tumors [28,[36][37][38]. The parotid gland is composed almost exclusively of serous type acini, and it is the most common site of AcCC (80% to 90% of cases); other reported sites are the palate (up to 15%), submandibular gland (4%), and sublingual gland (1%).…”
Section: Acinic Cell Carcinomamentioning
confidence: 99%
“…Likewise, there is no specific MRI signal distinguishing it from a benign tumor on conventional sequences [4]. On the other hand, as in the present case, dynamic perfusion sequences associated to diffusion-weighted sequences are able to suggest malignancy [8].…”
Section: Discussionmentioning
confidence: 41%
“…Two cases of a familial form were described, with a cytogenetic hypothesis based on findings of chromosomal mutations (in regions 4p, 5q, 6p, 17p [3,4] or 6q, Y-chromosome deletion [5]) probably involving tumor suppression genes. This malignant tumor is usually low-grade and slow-growth, and was long considered benign [6]; it is usually revealed by a parotid swelling, which may be painful or sensitive (in 10 to 50% of cases [2,4]), or associated with facial palsy (in 3 to 7% of cases [4,7]). There are more aggressive dedifferentiated forms [6] and prognosis is dependent on histologic type, which in turn correlates with risk of metastasis [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(9) Contradictory to the previous concept that IHC has limited role in the diagnosis of acinic cell carcinoma. (6) studies by Chenevert et al (5) has showed that DOG1 staining can be utilized to support the diagnosis of acinic cell carcinoma. In a study of 14 cases of salivary gland acinic cell carcinoma by Ihab Shafek Atta et al, all ACCs (100%) revealed positivity with DOG1 staining and the authors concluded that DOG1 has a higher efficacy in the diagnosis of ACC than α-amylase.…”
Section: Discussionmentioning
confidence: 99%